The FOIL methodology application for a humanist management in law offices - Netto, Nizio Maia (2023)
This research has the objective of studying the humanistic management of the law offices in the FOIL methodology perspective. This work presents the comprehension about the lawyer concept of the Federation Constitution and Lawyer Estatute points of view, comparing with the ontopsycological paradigm. Beyond presenting how this lawyer can act in the labor market, and which are his possibilities to act with excellence and effectiveness in the management of his workspaces, with his employees and posterior FOIL and Ontopsycology contributions to this model of management. Presenting how the lawyer can build himself as a person, jurist, businessman with function and value for himself, his employees, his clients and his society.